William Jay : abolitionist and anticolonialist - Budney, Stephen P., 1950- (Praeger Publishers, 2005)
A founder of the New York Anti-Slavery Society, William Jay was one of the most prolific and influential abolitionists of his day, yet Americans know little about him. This is the first extensive examination of his life and work in over 100 years. Like many of his contemporaries, Jay looked at a rapidly changing America and it frightened him. As a conservative social reformer, it was not merely sinfulness that alarmed Jay, but the perception that America was betraying its founding principles. From his early involvement in local temperance societies to his conversion to the cause of immediate a.